Transitivity and Appraisal Systems of the Online Reviews on Madura Religious Tourism Destinations - Ekawati, Rosyida; Puspitasari, Desi; Hanifa, Siti (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
This study observes the way the visitors express their appraisal in reviews of religious tourism and the linguistic resources they have choosen for their intentions. Further, it identifies the interaction of transitive and appraisal systems of the online reviews, that is, the processes utilized by the appraiser in their reviews and the way the processes are conected to the expressions of appraisal in the clauses and sentences in those reviews. The reviews are available online from Tripadvisor, https://www.tripadvisor.com/Attraction_Review. Each review that contains of transitivity and appraisal systems is analyzed based on types of processes originally taken from Halliday and Matthiessen (2004) and the appraisal system proposed by Martin and White (2005). There are absences of transitivity system of verbal and behavioral processes. For appraisal system, there are no judgement and engagement. The interaction of transitivity and appraisal systems relates to lexicogrammatical aspects that are utilized to highlight the interdependence of - and continuity between - vocabulary (lexis) and syntax (grammar). It brings out a connection between both the ideational and interpersonal functions of the language.